Qualitative Research Methods to Advance Research on Health Inequities Among Previously Incarcerated Women Living With HIV in Alabama. (October 2017) - Sprague, Courtenay; Scanlon, Michael L.; Pantalone, David W.
Justice-involved HIV-positive women have poor health outcomes that constitute health inequities. Researchers have yet to embrace the range of qualitative methods to elucidate how psychosocial histories are connected to pathways of vulnerability to HIV and incarceration for this key population. We used life course narratives and intersubjectivity—predicated on interview dialogue—to investigate how familial and social settings established their social patterning of HIV, incarceration risk, and poor health. Working with two Alabama community-based organizations, we recruited and interviewed 24 HIV-positive cisgender women with cyclical incarceration. We analyzed the data by charting women's life histories and conducting iterative content analyses. Participants described chaotic home environments, marked by exposure to trauma in childhood. The majority experienced repeated sexual and physical abuse that went undiagnosed and untreated until adulthood. Adolescence and young adulthood were characterized by onset of substance use, violent intimate partnerships, and subsequent behavioral and mental health problems. In adulthood, risk behaviors persisted for decades and women lacked mental health treatment and social support. Life course narratives and intersubjectivity contributed to knowledge by affording agency to marginalized participants to reflect on and narrate their life stories; instilling needed trust for researchers to investigate the complex risk pathways and psychosocial histories with this population; illuminating the nature, timing, sequence, and frequency of events underlying women's vulnerability and exposure to HIV and incarceration; and clarifying that early shaping events in childhood are connected to later risk environments and behaviors in adolescence and adulthood, suggesting the need for earlier interventions than are typically proposed.